The Effect of Eucheuma cottonii Seaweed Flour Addition on the Preference Level of Dogol Shrimp Nuggets - Hanun, Inas Maya Tamimah; Rostini, Iis; Haetami, Kiki; Pratama, Rusky Intan (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2025)
This study aims to determine the effect of adding Eucheuma cottonii seaweed flour on the preference level of dogol shrimp (Metapenaeus monoceros) nuggets. Dogol shrimp nuggets have high protein content but are low in fiber, so adding seaweed flour as a dietary fiber source is expected to improve the nutritional value and product quality. The research used an experimental method with four treatments of seaweed flour addition to dogol shrimp nuggets: 0% (control), 1.5%, 2.5%, and 3.5%. Hedonic testing was conducted with 25 semi-trained panelists as replicates to evaluate sensory attributes (color, aroma, taste, and texture). Based on panelist preference level and Bayes test results, the priority product was subsequently analyzed through proximate analysis (moisture, protein, fat, and ash), crude fiber content, and texture testing (Texture Profile Analysis). The research showed that adding seaweed flour significantly affected the increase in fiber content. The treatment with 1.5% seaweed flour addition was the best treatment with moisture content values of 61.11%; protein 8.47%; ash 1.84%; fat 1.78%; crude fiber 2.15%; and texture analysis values of hardness 4,315.7523 gForce; fracturability not detected; springiness 0.8487%; cohesiveness 0.5813%; gumminess 2,500.1247 gForce; chewiness 2,110.6553 gForce; and resilience 0.2553%. The addition of Eucheuma cottonii seaweed flour to dogol shrimp nuggets can serve as an innovation in developing healthier fishery product processing that consumers prefer